ROLE OF PONDOK PESANTREN EDUCATION AGAINST PREVENTION OF LGBT BEHAVIOR - Ahmad Miftahun Ni’am (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2018)
This study aims to find out: (1) How is the education system implemented byPondok Pesantren Minhajut Tamyiz Yogyakarta in preventing LGBT? (2) Whatis the role of the environmental Pondok Pesantren Minhajut Tamyiz Yogyakartain preventing LGBT? This study used descriptive qualitative method. This typeof research is the field research in which Pondok Pesantren Minhajut TamyizYogyakarta is the field studied by the author. The sampling technique used wassimple random sampling in which author randomly selected santri to be usedas samples. The method of data collection was carried out by interviews andobservations wherein the kiyai, ustadz, and some santri were used as interviewobjects, and the time taken for observation was on October 12 to November1, 2017. From the results of the study, the system was implemented and hedeveloped it at Pondok Pesantren Minhajut Tamyiz Yogyakarta which combinesthe knowledge of Religion and general skills. It is intended that students whograduate from Pondok Pesantren Minhajut Tamyiz Yogyakarta will have theprovision of religious knowledge and skills that are useful for future communityactivities. In the development of education in Pondok Pesantren Minhajut TamyizYogyakarta realizing the formation of a complete human or santri, carried outwith an emphasis on religious education. With efforts to develop education inpondok pesantren that emphasize religious education can make the personalityof santri become intact, and can become a shield in preventing LGBT behavior inthis country. And our hopes for the future is santri can put into practice into thecommunity and practice the sciences that have been studied and prevent LGBTfrom entering into community lives.